Comprehensive Analysis of circRNA-Mediated ceRNA Regulatory Networks in relation to Recurrent Implantation Failure. (23rd August 2022) - Wang, Hanbing; Lv, Wei; Zhu, Yilin
Abstract : Recurrent implantation failure (RIF) is attributed to endometrial receptivity dysfunction with many unanswered questions. Up to now, there is no explanation for RIF, and therapeutic strategies are usually limited to supportive care. In this study, we differentially analyzed the raw data deposited in three eligible microarray datasets, GSE111974, GSE121219, and GSE147442 to screen DE-mRNAs, DE-miRNAs, and DE-circRNAs, respectively. The value of log2-fold change |log2FC| ≥ 1 and the adjusted p value < 0.05 were considered differentially expressed between RIF and fertile control. We found 350 DE-mRNAs, 43 DE-miRNAs, and 1968 DE-circRNAs between RIF and fertile control. The PPI network identified 6 hub genes with degree ≥10, KDR, AGT, POSTN, TOP2A, RRM2, and PTGS2, in RIF. KDR, AGT, POSTN, TOP2A, and RRM2 were downregulated in endometrial tissue samples of RIF compared with those of fertile control, while PTGS2 was upregulated in endometrial tissue samples of RIF compared with those of fertile control. According to the ceRNA hypothesis, 15 groups of ceRNA network based on 10 circRNAs, hsa_circ_001572, hsa_circ_001884, hsa_circ_001375, hsa_circ_001449, hsa_circ_000029, hsa_circ_001168, hsa_circ_000210, hsa_circ_001484, hsa_circ_001698, and hsa_circ_000089 were constructed in RIF. In conclusion, the present study examined the possible role of circRNAs and their related ceRNA network involved in the pathogenesis of RIF.